THE COMPLICATIONS AND DRAWBACKS OF MEDICAL EVIDENCE IN CASES OF SEXUAL ASSAULT (Maharaja Surajmal Institute Law Journal, 2024)
With the steady rise in rape cases in India but only a 27.2% conviction rate, there arises a need to look at shreds of evidence that may strengthen the case for prosecution. One such is the medical report of the rape victim. Section 164A of the CRPC provides for a medical examination of the rape victim within 24 hours. The findings from the medical examination are used as corroborative evidence in the court of law u/s 45 of the Evidence Act. However, the investigative authorities often fail to present medical reports and are seldom punished. When such a report is not available, it is uncertain how and when can, its absence hinders the outcome of the case. Even though there are numerous medical jurisprudence textbooks, they remain out-dated and are based on a false sense of antiquated notions like women’s chastity and ability to resist as well as the irrelevant need for two-finger tests which have been debunked by newer research and advancement in the field of toxicology. However, despite such advancements, these textbooks are cited constantly by courts all across the nation leading to a higher rate of acquittal. Moreover, a report implying no injuries does not directly imply that the accused is innocent or vice versa. Furthermore, what happens when there is medical evidence, but the victim turns hostile owing to societal or financial pressure? The law remains ambiguous, and the precedents are constantly contradicting, which leads to the victim of a sexual assault paying the price as the offender goes unpunished owing to the irregularity on the subject. Therefore, this article aims to follow the complications and drawbacks of medical evidence in cases of sexual assault.
Keywords: Evidence; sexual assault; victim; human rights; injustice